Hubungan Kadar Gula Darah Sewaktu (GDS) Dengan Kadar Ureum Pada Pasien Diabetes Mellitus Tipe 2 Di Rumah Sakit Dr. H Bob Bazar Skm Lampung Selatan - Primastuti Feny Septianingtyas; Rina Kriswiastiny; Zulfian Zulfian; Deviani Utami (Universitas Malahayati, 2022)
ABSTRACT Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both (American Diabetes Association, 2017). DM is classified as a non-communicable disease where the sufferer is automatically unable to control the level of sugar in their blood. Globally, an estimated 422 million adults lived with diabetes in 2014, compared to 108 million in 1980. The International Diabetes Federation (IDF) Atlas 2017 reports that the DM epidemic in Indonesia is still showing an increasing trend. Type 2 DM in Indonesia itself is ranked seventh in the world after China, India, the United States, Brazil, Russia and Mexico. WHO predicts an increase in the number of DM sufferers in Indonesia by around 21.3 million in 2030 from 8.4 million in 2000. To determine the relationship between the time blood sugar levels value with urea levels in type 2 Diabetes mellitus patients at Hospital DR.H. Bob Bazar South Lampung in 2020. This type of research is correlative analytic with cross sectional method using purposive sampling as many as 201 samples of type 2 DM patients who meet the inclusion criteria. Data collection began in January 2021. The data used were secondary data in the form of medical records. The data were evaluated using the Spearman test. The research sample was 201 patients with type 2 diabetes with a minimum value of the GDS levels contained in the data 120 mg / dl, the maximum value of the GDS levels found in the data was 392 mg / dl and the average GDS level was 227 mg / dl, for urum levels. The highest urea level values found in the data were 117, the lowest urea levels were found in data 13 and the mean urea levels were 44.32. The results of the Spearman correlation obtained the value of p = 0.000 and the value of r = 0.695, because the value of p = 0.000 <0.05 so that it can be stated that Ha is accepted and Ho is rejected, then there is a relationship between the two variables studied, with r = 0.695 which means that there is a relationship or relationship strong between GDS levels and urea levels in type 2 DM patients at the DR. H. Bob Bazar, SKM South Lampung in 2020. There is a relationship between GDS levels and Ureum levels in type 2 DM patients at DR.H Hospital. Bob Bazar, SKM South Lampung in 2020 with results of p = 0.000 and r = 0.695. Keywords: Diabetes Mellitus, Time Blood Sugar Levels , Urea ABSTRAK Diabetes Mellitus (DM) adalah suatu kelompok penyakit metabolik dengan karakteristik hiperglikemia yang terjadi akibat kelainan sekresi insulin, kerja insulin, atau keduanya (American Diabetes Association, 2017). DM tergolong penyakit yang tidak menular dimana penderitanya secara otomatis tidak dapat mengendalikan tingkat gula dalam darahnya. Secara global, diperkirakan 422 juta orang dewasa hidup dengan diabetes pada tahun 2014, dibandingkan dengan 108 juta pada tahun 1980. International Diabetes Federation (IDF) Atlas 2017 melaporkan bahwa epidemi DM di Indonesia masih menunjukkan kecenderungan yang meningkat. DM tipe 2 di Indonesia sendiri menduduki peringkat ketujuh didunia setelah China, India, Amerika serikat, Brazil, Rusia dan Mexico. WHO memprediksikan kenaikan jumlah penderita DM di Indonesia sekitar 21,3 juta pada tahun 2030 dari 8,4 juta pada tahun 2000. Tujuan Untuk mengetahui hubungan antara nilai GDS dengan kadar ureum pada pasien DM tipe 2 di Rumah Sakit DR.H. Bob Bazar Lampung Selatan tahun 2020. Jenis Penelitian ini adalah analitik korelatif dengan metode cross sectional menggunakan purposive sampling sebanyak 201 sampel pasien DM tipe 2 yang memenuhi kriteria inkulsi. Pengambilan data dimulai pada bulan Januari 2021. Data yang digunakan yaitu data sekunder berupa rekam medik. Data dievaluasi dengan uji Spearman. Didapatkan sampel penelitian berjumlah 201 pasien DM tipe 2 dengan nilai minimal dari Kadar GDS yang terdapat di data 120 mg/dl , nilai maksimal dari kadar GDS yang terdapat di data 392 mg/dl dan rerata Kadar GDS yaitu 227 mg/dl, untuk kadar urum didapatkan nilai kadar ureum yang tertinggi yang terdapat di data yaitu 117 , nilai terendah kadar ureum yang terdapat di data 13 dan nilai rerata kadar ureum adalah 44.32 . hasil korelasi Spearman didapatkan nilai p=0,000 dan nilai r=0,695, karena nilai p=0,000 < 0,05 sehingga dapat dinyatakan Ha diterima dan Ho ditolak maka terdapat hubungan antara kedua variabel yang diteliti, dengan r=0,695 dapat diartikan terdapat hubungan atau berhubungan kuat antara kadar GDS dengan kadar ureum pada pasien DM tipe 2 di Rumah Sakit DR. H. Bob Bazar, SKM Lampung Selatan tahun 2020. Terdapat hubungan antara kadar GDS dengan Kadar Ureum pada pasien DM tipe 2 di Rumah Sakit DR.H. Bob Bazar, SKM Lampung Selatan tahun 2020 dengan hasil p=0,000 dan r = 0,695. Kata Kunci: Diabetes Mellitus, Kadar GDS, kadar ureum